Uji Efektivitas Ekstrak Umbi Tanaman Kembang Sungsang (Gloriosa Superba L.) Sebagai Nematisida Nabati terhadap Nematoda Puru Akar (Meloidogyne Spp.) pada Tanaman Tomat (Lycopersicum Esculentum Mill) - Nindi G. Isura Sitepu; I Dewa Putu Singarsa; I Made Sudana (Fakultas Pertanian, Universitas Udayana, 2024)
Root-knot nematodes (Meloidogyne spp.) are one of the nuisance organisms in crop cultivation, including tomato plants. This nematode resides in the root part of the plant. Nematode attacks result in decreased productivity, death and crop failure. One of the nematode control efforts that can be done is using botanical nematicides. Based on this, a botanical nematicide study was conducted for root-knot nematodes (Meloidogyne spp.) using extracts of breeches flower plant tubers (Gloriosa superba L.) with concentrations of 5%, 10% and 20%. This study used a completely randomized design (CRD) with 5 treatments, each treatment was repeated 6 times. Stages of research methods: (1) Preparation of tuber extract, (2) Preparation of Meloidogyne spp. solution, (3) Test the ability of extracts in pots / polybags. The purpose of this study was to determine the effectiveness of tuber extracts from breeches flower that can suppress the population of Meloidogyne spp. The results showed that the population of nematodes/300g of soil at 20% concentration had the best ability to suppress the population of root-knot nematodes by 15 tails (56.73%), 10% extract by 24.17 tails (30.28%), 5% extract by 32.50 tails (6.25%). In the calculation of nematode population/1 g of roots, 20% extract has the best ability to suppress the population of root puncture nematodes by 19.33 tails (71.43%), then 10% extract by 26.17 tails (61.32%), 5% extract by 31.83 tails (52.96%).